Treatment modalities for early management of class III skeletal malocclusion: A case series - Heena Sarangal; Ritu Namdev; Swati Garg; Natasha Saini; Parul Singhal (Wolters Kluwer Medknow Publications, 2020)
The characteristic features of Class III malocclusion are present at an early age, usually between 3 and 5 years of age. If left untreated, the Class III malocclusion or severe anterior crossbite may worsen, with the majority of these patients ultimately requiring orthognathic surgery as adults. The treatment in all developing Class III cases should be undertaken as soon as the abnormality is diagnosed to prevent it from becoming permanent and resulting in a full-blown Class III malocclusion. It provides more pleasing facial esthetics (the lip posture and facial appearance), thus improving the psychosocial development of a child. Various treatment options available for the management of developing Class III malocclusion are as follows: (1) functional appliances such as reverse twin block, Frankel appliance, and the removable mandibular retractor; (2) orthopedic appliances such as chin cap and face mask; and (3) orthodontic appliances, namely removable maxillary expansion plate or fixed orthodontic appliance with expanded upper arch wire. A treatment plan may be chosen depending on the amount of maxillary growth restriction, mandibular plane angle, the soft-tissue profile, and the age of the patient. This article discusses the various treatment options and the decision-making for different clinical cases based on the clinical features with a description of four different treatment approaches.